Penerapan Metode Fuzzy Tsukamoto Dalam Penentuan Jumlah Produksi Benang - Devie Firmansyah; Neng Erika Rustiani (Journal of Business Computers, 2021)
PT. Dhanar Mas Concern (DMC) is a textile company that specializes in the manufacture of Spining Yarns and Greige fabrics. Apart from being a leading supplier to the domestic market, PT. DMC sells several products to various countries. The problem that arises is the instability of the amount of sales that increases at a certain time, but there can also be a significant decrease in sales, this makes it difficult to determine the right amount of production and affects the level of losses due to the lack of raw material inventory, due to very low production quantities. , as well as the large amount of inventory because the amount of uncontrolled production as well as the aspects of workers and the number of machines also affects the creation process. Application of the Tsukamoto fuzzy method to determine the amount of yarn production based on inventory data and the amount of demand. From the results of the tests that have been carried out, it can be seen that from the data on the amount of yarn production in 2019 which has been analyzed, the results of the calculation of the mean absolute percentage error (MAPE) method = -3.85% are considered very good.